Study of snake bite cases admitted in tertiary care hospital in Nagpur - Bhelkar, Sandeep M.; Chilkar, Sanjay D.; Morey, Suresh M. (International Journal Of Community Medicine And Public Health, 2017)
Background: In developing countries major portion of individuals bitten by snakes first consult traditional practitioners before visiting a medical centre and resulting delay in transportation leads to mortality. Present study planned to study clinical features and epidemiological factors in snake bite cases. Methods: Hospital based cross sectional study was planned including all snake bite cases admitted during study period. Epi Info 7 used for analysis. Results: Out of 156 snake bite patients, 66.04% subjects were from month of July to September (mean age 37.78 years). About 30.77% of study subjects sought traditional healer for medical care, which was found to be significant when compared with not seeking treatment (Chi square =4.74, df =1, P =0.029). Maximum study subject i.e. 52 (33.33%) received ASV within 1 hour. Only 85 (54.49%) subjects reached the tertiary care hospital within 1- 6 hours following the bite. Mortality was higher in urban area as compared to rural area (P =0.104). Death was higher who had bites on upper limb (11.67%) as compared to bite on lowers limb (2.08%) (P =0.012). Proportion death was higher among those who did not received first Aid measures or took herbal medicine (P =0.022). Mortality was significantly higher in study subjects with complications such as cellulitis and DIC (P =0.006). Conclusions: Mortality among those who received first aid before coming to the hospital was lower (5.56%). Mortality was higher (6.25%) in cases where time interval between bite and initiation of treatment was more than 6 hours.